The Actual Challenges of Biologics Treatment in Patients with Psoriasis - Andrey L. Bakulev (State Scientific Center of Dermatovenereology and Cosmetology, 2020)
The article contain the main challenges meet doctors in real practice using biologics for treatment patients with psoriasis.Different aspects and concerns have been analised from new point of view: the aims of Bx therapy (incl. control of remission, personalized goals, etc.) primary and secondary responses, immunogenicity, treatment survival, retention rate or long lasting regain of response in psoriasis patients treated by biologics.